Peran E-Commerce Dan Gaya Hidup Dalam Menentukan Perilaku Konsumen - Moehadi; Hartiningsih Astuti; Siti Alfiyana; Kiswati Dewi Kartika (Jurnal Ilmiah Ekonomi Global Masa Kini, 2024)
Consumer behavior is all activities and psychology that motivate these activities before buying, purchasing products and services, using, consuming, after doing these things or evaluation activities. The factors that influence consumer behavior are mainly cultural factors, which include culture, subculture and social class. Two social factors are reference group, family, role, and status. Three personal factors consisting of age and stage, financial situation, work, lifestyle and personality. And finally, psychological factors include motivation, perception, knowledge, beliefs and attitudes. This research aims to analyze consumer behavior. Consumer behavior in this research is thought to be influenced by e-commerce and lifestyle. This research method was carried out using a descriptive quantitative analysis approach with primary data measured using a Likert scale. The research was conducted in the Bojonegoro University environment. This research was conducted on students of the economics faculty at Bojonegoro University. The sampling technique is based on a representative sample size, namely between 50-100 samples. Data analysis was carried out using several stages, namely testing data instruments, classical assumptions and multiple linear regression analysis. Based on the results of partial data analysis, e-commerce and lifestyle have a significant positive influence on consumer behavior. Meanwhile, e-commerce and lifestyle simultaneously influence consumer behavior. Then based on the R2 value of 0.888, it shows that e-commerce and lifestyle contribute to influencing consumer behavior by 88.8%.   Keywords: E-commerce, Lifestyle, Consumer Behavior